Late Quaternary hydroclimate variability in Madagascar and its connection to atmospheric circulation patterns - Christos Katrantsiotis; Simon Haberle; Anneli Ekblom; Rienk H. Smittenberg; Jan Risberg; Susan Rule; Geoff Clark; Atholl Anderson; Amy Prendergast; Aaron Carmens; Chantal Radimilahy; Lucien Rakotozafy; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Drift bottle data hint at large-scale ocean circulation changes - Natasha A. Ridenour; Liam Buchart; Eddy Carmack; Inge Deschepper; Eric Galbraith; Geoff Green; Juliana M. Marson; Clark Pennelly; Tahya Weiss-Gibbons; Paul G. Myers (Frontiers in Marine Science, 2023)
Over the last two decades, in an effort to engage youth in polar science, the Students On Ice (SOI; https://studentsonice.com/ ) project has become a platform for youth to partake in scientific expeditions around the globe. Among the various activities offered, youth are able to join cruises in the North Atlantic or Arctic, and drop sealed glass bottles into the ocean. Of the thousands that have been deployed, 5% of bottles have been recovered and reported back to SOI with details on when and where they were found. Here, we compare the observational bottle data with virtual particle trajectories from a high resolution regional ocean model. Although modelling results indicate a higher likelihood of bottles reaching the shores of the western Atlantic, the majority of recovered bottles were found on the eastern side of the Atlantic. We attribute this disparity to differences in population density in Canada and Europe, biasing the recovery rates. Despite this bias, we find that changes in recovery locations over time are consistent with changes in the main ocean currents associated with the contraction and expansion of the North Atlantic Subpolar Gyre, as simulated in our ocean model. In 2007, a large number of bottles were found in Norway, coinciding with a contracted North Atlantic Subpolar Gyre during 2004-2008. While between 2012-2016, the majority of bottles were recovered on the British Isles, during a time of gyre expansion. These results underline the importance of large scale oceanic cycles for tracking marine debris and pollution, and show how even simple data collection methods, such as drift bottles, can provide clues to the changes in the large scale ocean circulation.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Pattern, style and timing of British–Irish Ice Sheet advance and retreat over the last 45 000 years: evidence from NW Scotland and the adjacent continental shelf - Tom Bradwell; Derek Fabel; Chris D. Clark; Richard C. Chiverrell; David Small; Rachel K. Smedley; Margot H. Saher; Steven G. Moreton; Dayton Dove; S. Louise Callard; Geoff A. T. Duller; Alicia Medialdea; et al. (Journal of Quaternary Science, 2021)
Predicting the future response of ice sheets to climate warming and rising global sea level is important but difficult. This is especially so when fast‐flowing glaciers or ice streams , buffered by ice shelves, are grounded on beds below sea level. What happens when these ice shelves are removed? And how do the ice stream and the surrounding ice sheet respond to the abruptly altered boundary conditions? To address these questions and others we present new geological, geomorphological, geophysical and geochronological data from the ice‐stream‐dominated NW sector of the last British–Irish Ice Sheet (BIIS). The study area covers around 45 000 km 2 of NW Scotland and the surrounding continental shelf. Alongside seabed geomorphological mapping and Quaternary sediment analysis, we use a suite of over 100 new absolute ages (including cosmogenic‐nuclide exposure ages, optically stimulated luminescence ages and radiocarbon dates) collected from onshore and offshore, to build a sector‐wide ice‐sheet reconstruction combining all available evidence with Bayesian chronosequence modelling. Using this information we present a detailed assessment of ice‐sheet advance/retreat history, and the glaciological connections between different areas of the NW BIIS sector, at different times during the last glacial cycle. The results show a highly dynamic, partly marine, partly terrestrial, ice‐sheet sector undergoing large size variations in response to sub‐millennial‐scale climatic (Dansgaard–Oeschger) cycles over the last 45 000 years. Superimposed on these trends we identify internally driven instabilities, operating at higher frequency, conditioned by local topographic factors, tidewater dynamics and glaciological feedbacks during deglaciation. Specifically, our new evidence indicates extensive marine‐terminating ice‐sheet glaciation of the NW BIIS sector during Greenland Stadials 12 to 9 – prior to the main ‘Late Weichselian’ ice‐sheet glaciation. After a period of restricted glaciation, in Greenland Interstadials 8 to 6, we find good evidence for rapid renewed ice‐sheet build‐up in NW Scotland, with the Minch ice‐stream terminus reaching the continental shelf edge in Greenland Stadial 5, perhaps only briefly. Deglaciation of the NW sector took place in numerous stages. Several grounding‐zone wedges and moraines on the mid‐ and inner continental shelf attest to significant stabilizations of the ice‐sheet grounding line, or ice margin, during overall retreat in Greenland Stadials 3 and 2, and to the development of ice shelves. NW Lewis was the first substantial present‐day land area to deglaciate, in the first half of Greenland Stadial 3 at a time of globally reduced sea‐level c. 26 ka bp , followed by Cape Wrath at c. 24 ka bp. The topographic confinement of the Minch straits probably promoted ice‐shelf development in early Greenland Stadial 2, providing the ice stream with additional support and buffering it somewhat from external drivers. However, c. 20–19 ka bp , as the grounding‐line migrated into shoreward deepening water, coinciding with a marked change in marine geology and bed strength, the ice stream became unstable. We find that, once underway, grounding‐line retreat proceeded in an uninterrupted fashion with the rapid loss of fronting ice shelves – first in the west, then the east troughs – before eventual glacier stabilization at fjord mouths in NW Scotland by ~17 ka bp. Around the same time, ~19–17 ka bp , ice‐sheet lobes readvanced into the East Minch – possibly a glaciological response to the marine‐instability‐triggered loss of adjacent ice stream (and/or ice shelf) support in the Minch trough. An independent ice cap on Lewis also experienced margin oscillations during mid‐Greenland Stadial 2, with an ice‐accumulation centre in West Lewis existing into the latter part of Heinrich Stadial 1. Final ice‐sheet deglaciation of NW mainland Scotland was punctuated by at least one other coherent readvance at c. 15.5 ka bp , before significant ice‐mass losses thereafter. At the glacial termination, c. 14.5 ka bp , glaciers fed outwash sediment to now‐abandoned coastal deltas in NW mainland Scotland around the time of global Meltwater Pulse 1A. Overall, this work on the BIIS NW sector reconstructs a highly dynamic ice‐sheet oscillating in extent and volume for much of the last 45 000 years. Periods of expansive ice‐sheet glaciation dominated by ice‐streaming were interspersed with periods of much more restricted ice‐cap or tidewater/fjordic glaciation. Finally, this work indicates that the role of ice streams in ice‐sheet evolution is complex but mechanistically important throughout the lifetime of an ice sheet – with ice streams contributing to the regulation of ice‐sheet health but also to the acceleration of ice‐sheet demise via marine ice‐sheet instabilities.

Timing and pace of ice‐sheet withdrawal across the marine–terrestrial transition west of Ireland during the last glaciation - Colm Ó Cofaigh; S. Louise Callard; David H. Roberts; Richard C. Chiverrell; C. K. Ballantyne; David J. A. Evans; Margot Saher; Katrien J. J. Van Landeghem; Rachel Smedley; Sara Benetti; Matthew Burke; Chris D. Clark; et al. (Journal of Quaternary Science, 2021)
Understanding the pace and drivers of marine‐based ice‐sheet retreat relies upon the integration of numerical ice‐sheet models with observations from contemporary polar ice sheets and well‐constrained palaeo‐glaciological reconstructions. This paper provides a reconstruction of the retreat of the last British–Irish Ice Sheet (BIIS) from the Atlantic shelf west of Ireland during and following the Last Glacial Maximum (LGM). It uses marine‐geophysical data and sediment cores dated by radiocarbon, combined with terrestrial cosmogenic nuclide and optically stimulated luminescence dating of onshore ice‐marginal landforms, to reconstruct the timing and rate of ice‐sheet retreat from the continental shelf and across the adjoining coastline of Ireland, thus including the switch from a marine‐ to a terrestrially‐based ice‐sheet margin. Seafloor bathymetric data in the form of moraines and grounding‐zone wedges on the continental shelf record an extensive ice sheet west of Ireland during the LGM which advanced to the outer shelf. This interpretation is supported by the presence of dated subglacial tills and overridden glacimarine sediments from across the Porcupine Bank, a westwards extension of the Irish continental shelf. The ice sheet was grounded on the outer shelf at ~26.8 ka cal bp with initial retreat underway by 25.9 ka cal bp. Retreat was not a continuous process but was punctuated by marginal oscillations until ~24.3 ka cal bp. The ice sheet thereafter retreated to the mid‐shelf where it formed a large grounding‐zone complex at ~23.7 ka cal bp. This retreat occurred in a glacimarine environment. The Aran Islands on the inner continental shelf were ice‐free by ~19.5 ka bp and the ice sheet had become largely terrestrially based by 17.3 ka bp. This suggests that the Aran Islands acted to stabilize and slow overall ice‐sheet retreat once the BIIS margin had reached the inner shelf. Our results constrain the timing of initial retreat of the BIIS from the outer shelf west of Ireland to the period of minimum global eustatic sea level. Initial retreat was driven, at least in part, by glacio‐isostatically induced, high relative sea level. Net rates of ice‐sheet retreat across the shelf were slow (62–19 m a −1 ) and reduced (8 m a −1 ) as the ice sheet vacated the inner shelf and moved onshore. A picture therefore emerges of an extensive BIIS on the Atlantic shelf west of Ireland, in which early, oscillatory retreat was followed by slow episodic retreat which decelerated further as the ice margin became terrestrially based. More broadly, this demonstrates the importance of localized controls, in particular bed topography, on modulating the retreat of marine‐based sectors of ice sheets.

The evolution of the terrestrial‐terminating Irish Sea glacier during the last glaciation - Richard Christopher Chiverrell; Geoff Stephen Powell Thomas; Matthew Burke; Alicia Medialdea; Rachel Smedley; Mark Bateman; Chris Clark; Geoffrey A. T. Duller; Derek Fabel; Geraint Jenkins; Xianjiao Ou; Helen Marie Roberts; et al. (Journal of Quaternary Science, 2021)
Here we reconstruct the last advance to maximum limits and retreat of the Irish Sea Glacier (ISG), the only land‐terminating ice lobe of the western British Irish Ice Sheet. A series of reverse bedrock slopes rendered proglacial lakes endemic, forming time‐transgressive moraine‐ and bedrock‐dammed basins that evolved with ice marginal retreat. Combining, for the first time on glacial sediments, optically stimulated luminescence (OSL) bleaching profiles for cobbles with single grain and small aliquot OSL measurements on sands, has produced a coherent chronology from these heterogeneously bleached samples. This chronology constrains what is globally an early build‐up of ice during late Marine Isotope Stage 3 and Greenland Stadial (GS) 5, with ice margins reaching south Lancashire by 30 ± 1.2 ka, followed by a 120‐km advance at 28.3 ± 1.4 ka reaching its 26.5 ± 1.1 ka maximum extent during GS‐3. Early retreat during GS‐3 reflects piracy of ice sources shared with the Irish‐Sea Ice Stream (ISIS), starving the ISG. With ISG retreat, an opportunistic readvance of Welsh ice during GS‐2 rode over the ISG moraines occupying the space vacated, with ice margins oscillating within a substantial glacial over‐deepening. Our geomorphological chronosequence shows a glacial system forced by climate but mediated by piracy of ice sources shared with the ISIS, changing flow regimes and fronting environments.

Glacial Lake Pickering: stratigraphy and chronology of a proglacial lake dammed by the North Sea Lobe of the British–Irish Ice Sheet - David J. A. Evans; Mark D. Bateman; David H. Roberts; Alicia Medialdea; Laura Hayes; Geoff A. T. Duller; Derek Fabel; Chris D. Clark (Journal of Quaternary Science, 2017)
We report the first chronology, using four new optically stimulated luminescence dates, on the sedimentary record of Glacial Lake Pickering, dammed by the North Sea Lobe of the British–Irish Ice Sheet during the Dimlington Stadial (24–11 ka cal BP). Dates range from 17.6 ± 1.0 to 15.8 ± 0.9 ka for the sedimentation of the Sherburn Sands at East Heslerton, which were formed by multiple coalescing alluvial fans prograding into the falling water levels of the lake and fed by progressively larger volumes of debris from the Wolds. Fan formation ceased ∼15.8 ka, at a time when permafrost was degrading and nival‐fed streams were no longer capable of supplying sediment to the fans. A further age of 10.1 ± 0.7 ka dates the reworking of coversand into the early part of the Holocene, immediately post‐dating Younger Dryas periglacial structures. A 45‐m lake level dates to ∼17.6 ka, when the North Sea Lobe was already in retreat, having moved eastward of the Wykeham Moraine; it stood further east at the Flamborough Moraine by ∼17.3 ka. The highest (70 m) lake level and the occupation of the Wykeham Moraine date to an earlier phase of the North Sea Lobe occupation of the Vale of Pickering.

Leaf physiology and morphology of Castanea dentata (Marsh.) Borkh., Castanea mollissima Blume, and three backcross breeding generations planted in the southern Appalachians, USA - Benjamin O. Knapp; G. Geoff Wang; Stacy L. Clark; Lauren S. Pile; Scott E. Schlarbaum (New Forests, 2014)

Micro-Oxygenation of Red Wine: Techniques, Applications, and Outcomes - Leigh M. Schmidtke; Andrew C. Clark; Geoff R. Scollary (Critical Reviews in Food Science and Nutrition, 2011)